(untitled) (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2020)
There are so many Islamic boarding schools in Indonesia that cannot be separated from the role and initial goals of pesantren in the world of education. The proliferation of pesantren encourages pesantren to make new innovations in packaging the education contained in the program that was designed at the beginning. Programs organized by Islamic boarding schools need evaluation. Evaluation is one of the important things to do to find out how far the success of the program being implemented is carried out. Various evaluation methods can be used, including the personnel assessment method, the future prediction method, the action method or follow-up study, the comparative causal method, the correlational method, the survey method, and the historical method. These methods can be applied in carrying out evaluations, adjusting to the program to be evaluated.